Analysis of the performance of finalist swimming athletes in Olympic Games: reaction time, partial time, speed, and final time - da Silva, J. K. F.; Enes, A. A. N.; Sotomaior, B. B.; Barbosa, M. A. R.; de Souza, R. O.; Osiecki, R. (Journal of Physical Education and Sport, 2020)
The aim of this study was to verify and compare the reaction time, swimming speed, partial- and final time of freestyle swimmers at the Beijing 2008 (B08), London 2012 (L12), and Rio 2016 Olympics (R16). 109 athletes (male (n = 57) and female (n = 52)), Olympics finalists were analyzed in the 100m, 200m, and 400m freestyle swimming events. ANOVA one-way multi-compare was used to verify the difference between reaction time (RT), partial time (PT), mean speed (MS), and final time (FT) in the analyzed Olympics. Statistical differences were found in the RT in the 100, 200, and 400m freestyle in females and 400m freestyle in males over the three Olympics, while for the mean speed the first 50 meters presented differences in the partial times, and for final time only the 100m female was different over the three Olympics. The race and partial time strategies had similar characteristics during the analyzed Olympics, while the reaction time of the athletes presented significant evolution over the Olympics.